La logistique feminine: les stragegies d’actualisation vocationelle ou familiale - Spain, Armelle; Bedard, Lucille (Canadian Journal of Counselling and Psychotherapy, 2011)
From an extensive analysis of research data, this article presents a conceptual model of different strategies used by first-time mothers facing integration of maternal and professional roles. The originality of this model lies in the source of the data, and in its global and lifespan perspectives. Drawn from narratives of an heterogeneous group of women, this model takes into account psychological and socio-cultural elements as experienced in their everyday lives. Also, this model is built on observations made over a five-year period. Finally, uses of this model are suggested beyond the realm of women's activities to study men and women career developments within a systemic family standpoint.